Capybara (Hydrochoerus hydrochaeris) exposure to Rickettsia in the Federal District of Brazil, a non-endemic area for Brazilian spotted fever - Quadros, Ana Paula Nunes de (2021)
In this study, whole blood samples and ticks were collected from 57 capybaras in recreational areas in the Federal District, Brazil, aiming to investigate the presence of Rickettsia spp. using polymerase chain reaction (PCR) and indirect immunofluorescence (IFAT) assays. None of the capybara blood samples yielded rickettsial DNA by PCR. Among 55 capybara serum samples tested by IFAT, 53 (96.3%) reacted to Rickettsia spp. Among these, 21 (39.6%) identified the R. bellii antigen as the probable antigen involved in a homologous reaction (PAIHR), whereas 2 (3.8%) identified the R. parkeri antigen. Ticks collected from capybaras were identified as 173 Amblyomma sculptum and 410 A. dubitatum, in addition to nine Amblyomma spp. larvae. A sample of 231 ticks was subjected to DNA extraction and PCR for Rickettsia species. None of 122 A. sculptum yielded rickettsial DNA. Molecular evidence of R. bellii was found in 25/108 (23.1%) and of Rickettsia sp. strain Cooperi (R. parkeri-like agent) in 2/108 (1.9%) of the A. dubitatum samples. These results suggest a greater exposure to R. bellii in these capybara populations, in addition to a more significant number of A. dubitatum, which might characterize the Federal District region as not endemic for Brazilian spotted fever.